TAXONOMY OF SOME PENNATE DIATOMS FROM KALLAR KAHAR LAKE, DISTRICT CHAKWAL, PAKISTAN - M. Munir; R. Qureshi; M. K. Laghari; M. Arshad; A. Khaliq Ch (Journal of Animal and Plant Sciences, 2013)
Kallar Kahar Lake, an inland brackish water body is situated in District Chakwal, Pakistan. This lake is rich in phytoplankton, but facing shortage of water inflow resultantly rapidly drying. Therefore it was worthwhile to record diatomic flora of the lake and its tributaries before extinction. During the survey, a total of 17 pennate diatoms belonging to 10 genera, 7 families and 5 orders were identified. Algal species such as Caloneis tenuis, C. schumanniana, C. bacillum, C. molaris, C. macedonica, C. undulata, Diadesmis confervaceoides, Diploneis elliptica, Entomoneis paludosa, Eunotia minor, Gomphonema parvulum var. parvulum, G. truncatum, Haslea spicula, Luticola cohnii, Mastogloia belaensis and Seminavis strigosa were new record for Pakistan. Based on results it can be concluded that conservation status of the newly reported species should be determined for their management in future
Keywords: Pennate diatom; Kallar Kahar Lake; District Chakwal; Brackish water